Supply Chain Model in Digital for Construction Management in Higher Education Institute - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research aim to develop and to evaluatethe supply chain model in digital for construction management in higher education institute. The sample groups were five experts in supply , five experts inInformation and technology and five experts in construction engineering. The research sample totalling fifteen experts. The research tool was questionnaire supply chain model in digital for construction management in higher education institutecomprises six main components, Many suppliers, manufacturer, distributors,retailers, customer.The data analyzed by using arithmetic mean and standard deviation. The assessment ofsupply chain model in digital for construction management in higher education institute.The results showed that the model was validated at a “high” level, suggesting thatsupply chain model in digital for construction management in higher education institutecould be used to develop digital.